Interação e mediação por meio de animações educacionais no ensino e aprendizagem dos números naturais e suas operações - Silva, Cristiane Mininel da (2021)
This dissertation aims to analyze the mediations and interactions that occur through educational animations during the teaching and learning process of natural numbers and their operations, especially regarding addition and subtraction for children enrolled in the 3rd year of Elementary School I. In this context, the format of educational animations is made from problem situations. Such mediations and interactions are directly related to the work developed in a school in São Paulo’s state, in 2020, during the COVID-19 pandemic period. 36 children aged 7 and 8 years participated. The question that led the research was defined as follows: How do interactions and mediations of students in the 3rd year of Elementary School take place in the format of educational animations in mathematics classes so that they can acquire new knowledge related to the concept of natural numbers and about addition and subtraction operations? The qualitative research is based on the theoretical and methodological assumptions of cultural-historical theory. Data was obtained based on the development of mathematical problem situations, presented in animated video format, called educational animation, which involves the conceptual nexus of natural numbers: positional value, grouping and addition and subtraction operations. The information obtained indicates that interactions and mediations occur when: 1) children have autonomy to explain their learning with the assistance of some technological supports, such as educational animations and the abacus, even in a difficult and pandemic context of COVID-19; 2) the organization of classes by the teacher leads to educational practice that considers communication, dialogue, collaboration as important aspects of pedagogical strategies to develop the teaching and learning process. In order to make these interactions and mediations take place satisfactorily, four educational videos were prepared, which are configured as educational products and potentialized this new communication that emerges, pulses, develops in favor of discovery and an engaging and innovative educational strategy with its effective inclusion in the classroom.